Effects of time, anticoagulant and detection channel on platelet count in ethylenediaminetetraacetic acid (EDTA)-dependent pseudothrombocytopenia - Zhang, Yu; Chen, Bei; Feng, Jiaoying; Yu, Wen; Liang, Wei; Li, Meifen; Zhai, Guanghua; Yan, Meina (PeerJ, 2025)
Background EDTA-dependent pseudothrombocytopenia (EDTA-PTCP) is an in vitro phenomenon that may lead to expensive, time-consuming, and invasive diagnostic procedures as well as unnecessary patient treatment. The purpose of this study was to explore the effects of time, anticoagulant and detection channel on the platelet (PLT) count of EDTA-PTCP samples, and to suggest a better method for correcting spurious low PLT counts. Methods In this study, 43 identified EDTA-PTCP samples were collected. The Sysmex XN-9100, Mindray BC-6900 and Mindray BC-5390 haematology analysers were used to test these EDTA-PTCP samples on the following detection channels at different time points: PLT count by impedance method (PLT-I), PLT count by optical method (PLT-O) and PLT count by fluorescent staining (PLT-F). Results EDTA-PTCP was time-dependent and small PLT agglutination occurred in most of the corresponding citrate-treated samples. Our results further demonstrated that the detection channel significantly affected the PLT count of the EDTA-PTCP samples. The XN-9100 PLT-F channel exhibited a greater dissociative effect than the XN-9100 PLT-I and PLT-O channels. Moreover, blood samples processed in the PLT-O channel of the Mindray hematology analyzer showed the highest PLT count in EDTA-K2 tubes compared to the other detection channels. Conclusion Our data showed that time, anticoagulant and detection channel significantly affected the PLT count in the EDTA-PTCP samples. For the EDTA-PTCP samples, the simplest retest method was to use the PLT-O channel of the Mindray automatic blood analyser within 30 min. In addition, changing the sodium citrate anticoagulant and using the XN-9100 PLT-F channel within 15 min were also suitable for correcting the spurious low PLT of the EDTA-PTCP samples.
Keywords: EDTA-PTCP; PLT clumps; Haematology analyser; Dissociation effect; PLT physiology